Correlation between biochemical indicators, dialytic efficiency and nutritional status of patients with chronic kidney disease (Research, Society and Development, 2022)
Patients with chronic kidney disease often have impairment of nutritional status and this factor can interfere with the quality of treatment, favoring a worse prognosis. The purpose of this study was to verify the association of biochemical indicators, dialytic efficiency and nutritional status patients with chronic kidney disease on hemodialysis. This is a cross-sectional study performed with patients from a kidney disease center in Belém of Pará. The nutritional status was determined through the evaluation of the body mass index (BMI), biochemical data (albumin, phosphorus, potassium, hemoglobin, urea and glucose), Kt/V and urea reduction rate (URR). Data were tabulated and analyzed using the bioestat, version 5.0 and for static analysis of data was performed the Spearman  correlation test considering a p